Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1186/s13063-016-1281-9
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal penile nerve block for rigid cystoscopy in men: study protocol for a randomized controlled trial

Abstract: BackgroundPain is common in men undergoing rigid cystoscopy. Even with the application of a lubricant containing 2 % lidocaine, about 76 % of men suffer from mild to severe pain when undergoing rigid cystoscopy. The most painful part of the procedure for men is when the cystoscope passes through the membranous urethra. Song et al. (Neurourol Urodyn 29:592–5, 2010) did autopsies on males and found that the dorsal nerve of the penis (DNP), the terminal branch of the pudendal nerve, innervates the membranous uret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…[ 25 , 26 , 31 ] Song et al [ 27 ] performed autopsies on males and found that the dorsal nerve of the penis (DNP), the terminal branch of the pudendal nerve, innervates the membranous urethra in 53.3% of specimens. [ 32 ] Thus based on this theoretical knowledge, we formed a hypothesis that CRBD could be prevented by PNB.…”
Section: Introductionmentioning
confidence: 99%
“…[ 25 , 26 , 31 ] Song et al [ 27 ] performed autopsies on males and found that the dorsal nerve of the penis (DNP), the terminal branch of the pudendal nerve, innervates the membranous urethra in 53.3% of specimens. [ 32 ] Thus based on this theoretical knowledge, we formed a hypothesis that CRBD could be prevented by PNB.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] Various approaches such as topical urethral analgesia, dorsal penile nerve block, sedation, and listening music therapy have been used to make this procedure more tolerable for patients. [5][6][7]23 Our results suggest that in rigid cystoscopy patients, hypnosis was effective in reducing anxiety and pain as measured by STAI and VAS, respectively, along with physiologic measures such as MAP and heart rate. This observation accords well with the likelihood that the anxiety and pain are often associated, providing a vicious cycle between the two.…”
Section: Hypnosis For Anxiety and Pain In Rigid Cystoscopymentioning
confidence: 63%
“…In fact, a study published by Gooran et al [17] reported that an injection of lidocaine into the glans with lidocaine gels into the urethra resulted in significantly pain relief than gel alone. Qiu et al's study [18] in 2016 also showed better pain relief with dorsal penile nerve block in addition to intraurethral gel injection.…”
Section: Discussionmentioning
confidence: 99%